2013
DOI: 10.1080/00222933.2012.716866
|View full text |Cite
|
Sign up to set email alerts
|

Autumn community structure in the shallow mixed layer of the subtropical South China Sea reveals a peculiar copepod and zooplankton assemblage

Abstract: The South China Sea is the world's largest marginal sea. To understand the zooplankton community structure during monsoon transition period we investigated the copepod composition, abundance and distribution at six stations along a transect line in the subtropical South China Sea during the autumn of 1999. In the present study, 22 major zooplankton taxa were found, with Noctilucales, calanoid copepods and poecilostomatoid copepods being the most abundant of the overall zooplankton counts. We identified a total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
1
5
1
Order By: Relevance
“…These results confirm copepods as the dominant mesozooplankton taxon in coastal areas of the SCS, the Pearl River estuary (Tan et al 2004), and the Malacca Strait (Yoshida et al 2006). Tseng et al (2012b) reported that Noctilucales were the dominant zooplankton group (RA of 42.55%) in surface waters of the northern SCS. A similar result was reported for Noctiluca scintillans (Macartney) Kofoid & Swezy, 1921, which was abundant (7310.39 ± 36,102.05 ind./m 3 , RA of 51.04%) in surface waters of the southwestern East China Sea (ECS) during a summer cruise (Tseng et al 2011b).…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…These results confirm copepods as the dominant mesozooplankton taxon in coastal areas of the SCS, the Pearl River estuary (Tan et al 2004), and the Malacca Strait (Yoshida et al 2006). Tseng et al (2012b) reported that Noctilucales were the dominant zooplankton group (RA of 42.55%) in surface waters of the northern SCS. A similar result was reported for Noctiluca scintillans (Macartney) Kofoid & Swezy, 1921, which was abundant (7310.39 ± 36,102.05 ind./m 3 , RA of 51.04%) in surface waters of the southwestern East China Sea (ECS) during a summer cruise (Tseng et al 2011b).…”
Section: Discussionsupporting
confidence: 70%
“…The present study recorded an average abundance in waters shallower than 100 m of 99.14 ± 97.84 ind./m 3 . This value is lower than that in Tseng et al (2012b) who recorded an average copepod abundance of 523.42 ± 262.82 ind./m 3 in surface waters of the northern SCS. Previous studies in the SCS reported that the dominant copepod species varied.…”
Section: Copepod Community Structurecontrasting
confidence: 44%
See 3 more Smart Citations